PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT. ASTRA INTERNATIONAL Tbk (STUDI KASUS DI BURSA EFEK INDONESIA): accounting & finance - Asep Suryana, SE., M.AK (P3M STIE PASIM Sukabumi, 2018)
This study aims to determine the effect of leverage (DR) and profitability (ROE) on firm value (PBV) at PT. Astra International Tbk. The data used in this study were obtained from the financial statements of PT. Astra International Tbk from 2007 to 2016. In this study the author uses the theory of Irham Fahmi (2014:135) for the effect of the title. This study aims to determine whether there is a significant and positive effect between leverage, profitability and firm value at PT. Astra International Tbk. The method used in this research is descriptive associative with causal study. Data analysis techniques used in this research are classical assumption test, multiple correlation, multiple regression test, and hypothesis testing. The classical assumption test consists of normality test, multicollinearity test, and heteroscedasticity test. While the hypothesis testing consists of t test (partially), f test (simultaneously) and R2 test (coefficient of determination). The results of the research PT. Astra International Tbk that simultaneously in testing the t-test hypothesis (partially) Leverage (DR) has no effect on Firm Value (PBV) with tcount < ttable = (1.370 < 2.36482) while Profitability (ROE) to Firm Value PBV) has a significant effect with the value of tcount < ttable = (2,450 > 2,036482). Then in testing the f test hypothesis (simultaneously) Leverage (DR) and Profitability (ROE) have no effect on Firm Value (PBV) with Fcount < Ftable = (3,089 < Ftable 4,74). And testing the hypothesis on the R2 test (coefficient of determination) that the results of the KD value = 46.9%, with a value of 46.9% and the remaining 53.1% which is explained by other factors not examined. So it can be concluded that the influence of leverage and profitability on firm value is included in the strong category.